Authentication Model on Cloud Computing - Rajesh Telrandhe, Swapnil; Kapgate, Deepak (International Journal of Computer Sciences and Engineering, 2014)
Cloud computing is an internet-based computing, where a set of resources and services such as applications, Storage and servers are delivered to computers and devices through the Internet. It incorporates large open distributed system, virtualization and internet delivery of services, dynamic provision of reconfigurable resources and on – demand operations. Cloud Computing is continuously growing and showing consistent growth in the field of computing. The major challenging task in cloud computing is the security and privacy issues caused by the outsourcing of infrastructure, sensitive data and critical applications and its multi- tenancy nature. The security for Cloud Computing is emerging area for research work and this paper discusses various types of authentication methods and multi-factor user authentication.